ANALYSIS ON THE USE OF SLANG ON EMINEM’S LYRICS - Hastuti Retno Kuspiyah (Channing : Journal of English Language Education and Literature, 2016)
This study concerns with the analysis of slang in Eminem’s song lyrics. This study proposes problem are What types of slang language are used in Eminem’s song lyrics?, and What are the meaning of those slang language used Eminem’s song lyrics?. Hopefully, this study will be useful for students of English Department, especially to help them understand slang language. Moreover, the purpose of this study is to find out the types of slang that is used by Eminem’s lyrics. Therefore, this analysis used descriptive method because it is to describe the meaning of slang language in Eminem song lyrics of slang language in them. The data were taken randomly, that there are ten song lyrics. Then, in this study the procedure used in the data collection are: (1) reading and comprehending the lyrics; (2) identifying the slang words used in the lyrics; (3) Marking the slang words found in the lyrics; (4) finding and classifying the meaning of the slang words. Based on the find, the writer found that there are five types of slang. There are cockney slang, society slang, workmen’s slang, and public house slang, slang in public school and university.